AKSES KESEHATAN PADA PEREMPUAN YANG DILACURKAN YANG MENGIDAP HIV/AIDS - Abdullah, Moch. Rizal; Pramana, Reynaldi Rafi; Sumiyati, Sumiyati (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas 17 Agustus 1945 Surabaya, 2020)
Human Immunodeficiency Virus / Acquired Immune Deficiency Syndrome (HIV / AIDS) is a deadly virusthat infects the human reproductive system due to unhealthy sexual relations. This journal discusses theregulations on access to health for prostituted women who have HIV / AIDS and from the aspect of humanrights and also the implementation of a ban on discrimination against people with HIV / AIDS, especially inthe health sector. HIV / AIDS itself has national and international safeguards as outlined in the form of lawsand regulations, or international conventions related to access to health for people with HIV / AIDS. Thispaper uses two types of methods, namely data collection methods and empirical normative. From the journalresults it can be concluded that the position of people with HIV / AIDS who are human beings who have theright should have the protection of human rights, real health service guarantees from the government, accessto proper health and the feasibility of getting work and life that should be the right of HIV / AIDS, not just aseries of regulatory writings without real action.